1994
DOI: 10.1017/s0890037x00039683
|View full text |Cite
|
Sign up to set email alerts
|

Giant Ragweed (Ambrosia trifida) Canopy Architecture and Interference Studies in Soybean (Glycine max)

Abstract: Field experiments were established at Columbus and near South Charleston, OH to determine the effects of giant ragweed population density on soybean yield and to characterize the development of giant ragweed grown in 76-cm soybean rows. An economic threshold was calculated for Ohio using a common treatment for giant ragweed control in soybean. A cost of $41/ha was estimated for a farmer to apply 0.56 kg/ha bentazon plus 0.28 kg/ha fomesafen plus COC (1.25% v/v). Assuming a soybean value of $0.22/kg, the cost o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 15 publications
3
90
0
Order By: Relevance
“…If the cost of hand weeding giant ragweed is similar to that for hand weeding palmer amaranth, planting wheat or alfalfa would become much more economical than found in this study since hand weeding was not required for these crops. If giant ragweed is allowed to compete with corn and soybean, corn yield can be reduced by up to 90% with 1.4 giant ragweed plants m -2 (Harrison et al, 2001) and soybean yield can be reduced by 45 to 77% with 1.0 giant ragweed plant m -2 (Webster et al, 1994). …”
Section: Herbicide-resistant Giant Ragweed Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the cost of hand weeding giant ragweed is similar to that for hand weeding palmer amaranth, planting wheat or alfalfa would become much more economical than found in this study since hand weeding was not required for these crops. If giant ragweed is allowed to compete with corn and soybean, corn yield can be reduced by up to 90% with 1.4 giant ragweed plants m -2 (Harrison et al, 2001) and soybean yield can be reduced by 45 to 77% with 1.0 giant ragweed plant m -2 (Webster et al, 1994). …”
Section: Herbicide-resistant Giant Ragweed Implicationsmentioning
confidence: 99%
“…Giant ragweed is one of the most competitive and problematic weeds aff ecting crop production in the midwestern United States and has recently developed resistance to multiple herbicide sites of action, including acetolactate synthase and 5-enolpyruvylshikimate-3-phosphate synthase inhibitors (Webster et al, 1994;Heap, 2016). Crop rotations with multiple years of alfalfa reduce herbicide-resistant giant ragweed emergence while maintaining a similar level of seed bank depletion as other crop rotations common to the midwestern United States (Goplen et al, 2017).…”
mentioning
confidence: 99%
“…Additionally, most of the GR weeds in the midwest are also resistant to ALS-inhibitors such as chlorimuron-ethyl, imazamox, imazaquin, imazethapyr, thifensulfuron-methyl (Legleiter & Bradley, 2008;Sarangi et al, 2015). example, in Missouri and Ohio, one giant ragweed plant per m -2 reduced soybean yield more than 45% (Baysinger & Sims, 1991;Webster et al, 1994). Similarly, Hager et al (2002) reported up to 43% reduction in soybean yield when common waterhemp interference was allowed to persist 4 wk or longer after soybean unifoliate leaf expansion.…”
Section: Introductionmentioning
confidence: 96%
“…Giant ragweed has caused corn (Zea mays L.) and soybean [Glycine max (L.) Merr.] grain yield losses ≥50% at a weed population density of 1 plant m -2 [4][5][6]. A 30% reduction in yield in soybean was observed in the presence of a common ragweed density of 1 plant per 1.5 m 2 [7].…”
Section: Introductionmentioning
confidence: 99%